ANALISIS KEMAMPUAN SISWA MENYELESAIKAN SIKLUS AKUNTANSI PERUSAHAAN JASA DI SMK NEGERI 8 PALEMBANG - Nopita Nopita; Neta Dian Lestari; Nova Pratiwi (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
AbstractAccounting is a compulsory subject given to accounting majors which contains material on the service company cycle.Â  The pattern of learning which has implemented so far at SMK Negeri 8 Palembang has been optimal.Â  Based on it, the problem in this study is how is the ability of students to complete the accounting cycle of service companies at SMK Negeri 8 Palembang. The purpose of this study was to determine the ability of students to complete the service company accounting cycle at SMK Negeri 8 Palembang.Â  The research method that is used is descriptive statistical method. The results showed that the level of students' ability to complete the service company's accounting cycle in the cognitive domain of students' abilities "Good" in completing the general journal, students' abilities were "Very good", student's ability ledger was "Very good", the balance sheet of students' abilities was "Very good", verse student ability adjustment journal â€œGoodâ€, student ability balance sheet â€œGoodâ€, student ability financial report â€œGoodâ€, student ability closing journal â€œGoodâ€, trial balance after closing student ability â€œGoodâ€, reversing journal student ability â€œGoodâ€. In the affective domain, the student's ability is "Good". Furthermore, in the psychomotor domain, the students' abilities are "Good".KeywordsÂ  : Analysis, student ability, accounting cycle, service company